2018
DOI: 10.1016/j.humov.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Motor learning and movement automatization in typically developing children: The role of instructions with an external or internal focus of attention

Abstract: The aim of the current study was to examine the effects of an external focus of attention (i.e., on the movement outcome) versus an internal focus of attention (i.e., on the movement itself) on motor learning in typically developing children. We examined both immediate motor performance (i.e., practice effect, when focus instructions are given) as well as motor performance after one week (i.e., learning effect). In addition, we examined if an external and an internal focus of attention differently affected mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 23 publications
3
27
0
4
Order By: Relevance
“…The current findings add important evidence to the increasing body of literature showing a lack, or an unexpected role of working memory for motor learning of children (Brocken, Kal, & van der Kamp, 2016;Jongbloed-Pereboom, Peeters, Overvelde, Nijihuis-van der Sanden, and Steenbergen (2015); Krajenbrink et al, 2018;van Abswoude, Nuijen et al, 2018;van Abswoude, van der Kamp, & Steenbergen, 2018). For example, in a recent study, van van Abswoude, van der Kamp et al, 2018 found only a small effect of visuospatial working memory capacity on performance during practice of an aiming task in an explicit context.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…The current findings add important evidence to the increasing body of literature showing a lack, or an unexpected role of working memory for motor learning of children (Brocken, Kal, & van der Kamp, 2016;Jongbloed-Pereboom, Peeters, Overvelde, Nijihuis-van der Sanden, and Steenbergen (2015); Krajenbrink et al, 2018;van Abswoude, Nuijen et al, 2018;van Abswoude, van der Kamp, & Steenbergen, 2018). For example, in a recent study, van van Abswoude, van der Kamp et al, 2018 found only a small effect of visuospatial working memory capacity on performance during practice of an aiming task in an explicit context.…”
Section: Discussionsupporting
confidence: 71%
“…Brocken et al (2016) also failed to show a role for working memory capacity on learning with an internal or external focus of attention, although they only investigated verbal working memory. Finally, in the studies of Krajenbrink et al (2018) and van van Abswoude, Nuijen et al (2018) there was also no role of working memory capacity for respectively learning over a one week period, and performance during practice, with internal or external focus instructions.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations